2021
DOI: 10.1113/ep089765
|View full text |Cite
|
Sign up to set email alerts
|

Remote liver injury following acute renal ischaemia–reperfusion: involvement of circulating exosomal miR‐687 and regulation by thymoquinone

Abstract: The pathophysiology of remote hepatic injury following acute renal ischaemiareperfusion injury (IRI) is of particular clinical interest. Secreted small non-coding microRNA (miRs) are thought to exist in exosome-encapsulated form. Thymoquinone (TQ) is the main bioactive ingredient of Nigella sativa and has several renoprotective actions. We expected exosomal miR-687 to be relevant as it could act as a humoral mediator, with possible modulation by TQ. Thirty adult male Wister albino rats were assigned to three g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“… 146 , 147 , 148 , 149 , 150 Administration of several cell-derived exosomes facilitates miRNA levels in ischemic kidney tissue or serum. Similarly, most studies on AKI injury have previously been performed using tissues or cells that were experimentally exposed to renal ischemia and reperfusion, 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 as described in Table 3 and Figure 5 and emphasized in the following sections.…”
Section: Roles Of Exosomal Mirnas In Renal Ischemia-reperfusion Injurymentioning
confidence: 99%
“… 146 , 147 , 148 , 149 , 150 Administration of several cell-derived exosomes facilitates miRNA levels in ischemic kidney tissue or serum. Similarly, most studies on AKI injury have previously been performed using tissues or cells that were experimentally exposed to renal ischemia and reperfusion, 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 as described in Table 3 and Figure 5 and emphasized in the following sections.…”
Section: Roles Of Exosomal Mirnas In Renal Ischemia-reperfusion Injurymentioning
confidence: 99%
“…Fei et al (2021) performed nextgeneration sequencing (NGS) of miRNAs in plasma-derived exosomes and verified that miRNAs-PC-3p-190-42101 in exosomes could reduce the levels of inflammatory factors and protect the liver from HIRI. In a rat model of HIRI, Ashour et al (2021) reported that plasma exosomes had increased levels of miR-687, in addition to increased levels of liver tissue inflammatory markers and caspase-3. Inhibiting the expression of exosomal miR-687 may protect against hepatic injury.…”
Section: Body Fluid-derived Exosomesmentioning
confidence: 99%